Using Technology-Mediated Board Game on Young Learners - Niluh Putu Puri Palupi Sukenasa; Ju-Ling Shih; Herman Dwi Surjono (Script Journal: Journal of Linguistics and English Teaching, 2020)
Background: The use of games and technology for educational purposes can be an appropriate method of enhancing learning performance. Therefore, this study presents a technology-mediated board game and its related course to engage young learners in Indonesia for learning English vocabulary. The study investigated young learners' vocabulary learning performance and learning motivation as the effects of using technology-mediated board game in the course. Methodology: This study employed a quasi-experimental design involving 67 students of one urban and one rural primary school. The vocabularies of fruits and vegetables were implemented online in the game by using QR codes. The instructional practices are to improve students' learning achievement and to find out students' learning motivation. The pre-test, post-test, and Keller's ARCS motivation model were conducted to analyze the effectiveness of technology-mediated board game for learning English vocabulary. Findings: The main finding indicated that technology-mediated board games could improve students' English vocabulary learning achievement. Moreover, the use of technology-mediated board games encouraged young learners to have strong learning motivation. On the other hand, the game could promote students to have a concept in gardening that can be encounter in their daily life. Conclusion: These findings imply that technology-mediated board game becomes an effective way of teaching English vocabulary to young learners in Indonesia.